Casein Kinase Iγ2 Impairs Fibroblasts Actin Stress Fibers Formation and Delays Cell Cycle Progression in G1 - Mathieu Latreille; Afnan Abu-Thuraia; Rossella Oliva; Dongmei Zuo; Louise Larose (International Journal of Cell Biology)
Actin cytoskeleton remodeling is under the regulation of multiple proteins with various activities. Here, we demonstrate that the γ2 isoform of Casein Kinase I (CKIγ2) is part of a novel molecular path regulating the formation of actin stress fibers. We show that overexpression of CKIγ2 in fibroblasts alters cell morphology by impairing actin stress fibers formation. We demonstrate that this is concomitant with increased phosphorylation of the CDK inhibitor p27Kip and lower levels of activated RhoA, and is dependent on CKIγ2 catalytic activity. Moreover, we report that roscovitine, a potent inhibitor of cyclin-dependent kinases, including Cdk5, decreases p27Kip protein levels and restores actin stress fibers formation in CKIγ2 overexpressing cells, suggesting the existence of a CKIγ2-Cdk5-p27Kip-RhoA pathway in regulating actin remodeling. On the other hand, we also show that in a manner independent of its catalytic activity, CKIγ2 delays cell cycle progression through G1. Collectively our findings reveal that CKIγ2 is a novel player in the control of actin cytoskeleton dynamics and cell proliferation.